Interaction of omeprazole with enteric-coated salicylate tablets - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 1998)
Objective: Enteric-coated tablets are designed to resist gastric fluids and to disrupt and dissolve in the alkaline medium of the small intestine. Main objective of the present study was to investigate whether the increase in gastric pH due to omeprazole treatment alters the release rate of a drug from enteric-coated formulation. To this end, we have compared the single dose pharmacokinetics of a single-unit enteric-coated salicylate to that of uncoated acetylsalicylic acid tablets in the presence and absence of omeprazole treatment. Methods. Study was carried out according to 4 x 4 Latin square design. Eight healthy subjects received either uncoated acetylsalicylic acid tablets or single-unit enteric-coated sodium salicylate tablets alone or following 4 days of treatment with single-dose 20 mg omeprazole, and blood samples were collected for 24 hours. Serum salicylate levels were determined by the modified spectrophotometric method of Brodie et al. [1994]. Results. Salicylate was absorbed rapidly from uncoated tablets but absorption of salicylate from enteric-coated tablets was delayed, as expected. According to our results, omeprazole treatment did not influence the bioavailability from uncoated acetylsalicylic acid tablets but the absorption rate of salicylate from enteric-coated tablets was increased significantly. Conclusion: Findings of the present study demonstrate that omeprazole treatment significantly increases the rate of absorption of single-unit enteric-coated medication. Enhanced rate of absorption is most probably due to an early disruption of enteric coating and the intragastric release of the drug secondary to an omeprazole-mediated increase in gastric pH. The results of the present study also corroborate previous findings which have demonstrated highly variable absorption of enteric-coated single units.
Keywords: omeprazole; salicylate; enteric coating; interaction; bioavailability; GASTRIC-ACIDITY; PHARMACOKINETICS; ABSORPTION; DIGOXIN